CULTURAL RESONANCE: PARALLELS AND DIVERGENCES IN UZBEK AND ENGLISH HEROIC EPICS - Rayimkulova Laylo Otabek qizi (KONFERENSIYALAR, 2025)
Annotation. This article investigates the people courageous legends of Uzbekistan and Britain, highlighting both the parallels and divergences in their story structures, topical components, and social importance. Through a comparative investigation, we look at how these legends reflect the interesting verifiable settings, societal values, and ethical lessons of the individual societies. By analyzing unmistakable works such as “Alpomish” from Uzbek old stories and “Beowulf” from English convention, we reveal how each epic serves as a vessel of social personality and communal values. This consider points not as it were to improve the understanding of these courageous accounts but too to demonstrate the all inclusive topics of mettle, honor, and the human encounter that rise above social boundaries.